1999
DOI: 10.1002/(sici)1097-4652(199905)179:2<193::aid-jcp9>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF?B in the regulation of macrophage colony stimulating factor by tumor necrosis factor-? in ST2 bone stromal cells

Abstract: Expression of MCSF in bone is important to the regulation of osteoclastogenesis. We show here that tumor necrosis factor-alpha (TNFalpha) increases the production of both soluble (sMCSF) and membrane-bound (mMCSF) macrophage colony stimulating factor by ST2 bone stromal cells. Treatment of ST2 cells with TNFalpha caused sMCSF levels to increase by 394+/-5% from basal; mMCSF rose by 316+/-66% from 30+/-10 per 100,000 cells in the same time. These increases were consistent with increased expression of mRNAs enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The human M‐CSF gene promoter was shown to be activated via its NF‐κB binding site in the presence of a pro‐inflammatory cytokine, TNF‐α, in HL60 cells (21) and in human osteoblast cells (22). On the other hand, using a mouse M‐CSF promoter construct, the TNF‐α‐induced NFκB p50/p60 complex formation did not stimulate the NF‐κB response element in the mouse stromal cell line St4 (23). Thus, the human M‐CSF gene promoter, but not mouse M‐CSF gene promoter, appears to be activated by inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…The human M‐CSF gene promoter was shown to be activated via its NF‐κB binding site in the presence of a pro‐inflammatory cytokine, TNF‐α, in HL60 cells (21) and in human osteoblast cells (22). On the other hand, using a mouse M‐CSF promoter construct, the TNF‐α‐induced NFκB p50/p60 complex formation did not stimulate the NF‐κB response element in the mouse stromal cell line St4 (23). Thus, the human M‐CSF gene promoter, but not mouse M‐CSF gene promoter, appears to be activated by inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…4C, TRAP activity dose dependently increased in proportion to the added sOPGL. ST-2 cells express mMCSF in the absence of 1,25D or Dex, as we have previously shown (11). To assure that a lower level of mMCSF expression also supported osteoclastogenesis, sOPGL was added to cocultures of ST-2 cells and BMMs in the absence of 1,25D or Dex.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these factors stimulate the expression of MCSF, leading to the hypothesis that the level of MCSF present within the local bone environment might dose dependently direct osteoclast formation. For instance, 1,25D, TNF-␣, and PTH, all of which potently induce osteoclast formation, cause increased secretion of sMCSF (11,24,31). Additionally, several investigators have suggested that estrogen deficiency might promote osteoclastogenesis by increasing the production of sMCSF by bone stromal cells (12,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that pretreatment with the antioxidant agent N-acetylcysteine suppresses LPSmediated production of TNF-a and PGE2 by resident lung macrophages and that NAC suppresses NF-k B activation associated with reactive oxygen species (Mendez et al 1995, Fox et al 1997, Isaacs et al 1999, Li et al 2000. NF-k B activation is a critical convergence point of the in ammatory, cytotoxic and cytokine/TNF-a expression modulating pathways (Schreck et al 1992).…”
Section: Discussionmentioning
confidence: 99%